1985
DOI: 10.1007/bf00582573
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of ?-adrenergic regulation of the Ca channel in the guinea-pig heart

Abstract: Dose-response relations for the increase in the amplitude of Ca current (ICa) on external application of isoprenaline (ISP) and internally applied cyclic AMP (cAMP) or catalytic subunit of cAMP-dependent protein kinase (C subunit) were established in single ventricular cells of the guinea pig. An intracellular dialysis technique was used. The threshold concentration was for ISP 10(-9) M, for cAMP 3 microM (pipette concentration to which 10(-5) M 3-isobutyl-1-methylxanthine was added) and for C subunit around 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
160
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 377 publications
(177 citation statements)
references
References 46 publications
17
160
0
Order By: Relevance
“…L-type Ca currents are often subject to extensive regulation./Ca L of TRCs might be directly under the control of a second messenger as, for instance, the betaadrenoreceptor pathway in cardiocytes (Kameyama et al, 1985;Pelzer et al, 1990). This possibility remained unexplored in this study.…”
Section: Two Types Of Ca Currentsmentioning
confidence: 49%
“…L-type Ca currents are often subject to extensive regulation./Ca L of TRCs might be directly under the control of a second messenger as, for instance, the betaadrenoreceptor pathway in cardiocytes (Kameyama et al, 1985;Pelzer et al, 1990). This possibility remained unexplored in this study.…”
Section: Two Types Of Ca Currentsmentioning
confidence: 49%
“…For example, Kameyama, Hofmann, and Trautwein (1985) showed that the nonhydrolyzable ATP analogue, ATP~/S, introduced into guinea pig ventricular myocytes via the pipette, enhanced both basal and Iso-stimulated wholecell Ca z+ currents (Kameyama et al, 1985;Kameyama, Hescheler, Hofmann, and Trautwein, 1986;Hescheler, Kameyama, and Trautwein, 1987), and slowed (Kameyama et al, 1985) or prevented (Hescheler et al, 1987) the current decline after washing out Iso, results consistent with thiophosphorylation of Ca 2+ channels rendering them relatively resistant to the normally strong activity of endogenous phosphatases.…”
Section: Comparison With Pka Regulation Of Cardiac Ca E+ Currentsmentioning
confidence: 61%
“…These effects of HF are similar to those seen in the presence of dihydropyridine calcium channel agonists [9-121 and less similar to those seen following phosphorylation of the calcium channel [5,7,13]. Inactivation of Ica is thought to consist of both voltage-and calcium-dependent components [ 141.…”
Section: Discussionmentioning
confidence: 82%